DEVELOPING ENGLISH MULTIMEDIA BASED TEACHING MEDIA BY USING MICROSOFT POWER POINT - Verawati; Luardini, Maria Arina; Asi, Natalina (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2020)
The purpose of this R&D was to develop an English multimedia based teaching media by using Microsoft power point as the demand of 2013 curriculum in the utilization of the ICT in the teaching learning process. The product of this research was interactive media with two different topics. The subject of this research was the tenth grade students of SMAN 1 Kuala Pembuang in academic year 2018/2019. The objective of this research was how to develop English multimedia based teaching media by using Microsoft power point for tenth graders. This research was conducted by using Research and Development Method (R and D) where the product was created and tried out to the subject. The instruments of this research were questionnaire, interview, expert validation, and observation which were handed out to the students, teacher and the experts. The data collected were analyzed qualitatively. The result of the need assessment and the interview showed that both the teacher and students required multimedia based teaching media which are relevant to their need and interest and the demand of 2013 curriculum about the utilization of ICT. The data collected from observation showed that media developed was appropriate for teaching writing descriptive text.